Antibacterial activity of Phoenix dactylifera L. (Date palm) Seeds Extract against Escherichia coli - Ado, A.,; Chonoko, U. G.; Abdul- Azeez, U. M. (UMYU Journal of Microbiology Research)
This research determines antibacterial activity of Phoenix dactylifera against clinical isolate of Escherichia coli. Extraction, phytochemical screening and agar diffusion methods were employed to evaluate phytochemical profile, and antibacterial activity of Phoenix dactylifera. Alkaloids, cardiac glycosides and saponnins are present in Phoenix dactylifera seeds. Phoenix dactylifera seeds showed activity against E. coli with zone of inhibition of 20.4mm. The Minimum inhibitory concentration (MIC) and Minimum bactericidal concentration (MBC) of Phoenix dactylifera seed extract are 1000µg/ml and 100µg/ml against E. coli respectively. Phoenix dactylifera seed could be very useful in the management of gastrointestinal infection due to E. coli.